Powering The Archipelago: Accelerating Rural Electrification in Indonesia with Community-based Renewable Energy - Wahono, Jaya; Wibowo, Djati; Nurhadiyanto, Mohammad Arif; Kartika, Surya Batara; Rizal, Irfansyah; Azmi, Abdul Luky Shohiful; Satriyo, Dodi Budi; Murbini, Adhi Nugroho (Mesin, 2017)
Large portion of the population in Indonesia lack access to electrical power, and 85% of these portion live in rural areas. This lack of access to electrical power means also lack of access to peopleâs fundamental needs. In addition, local industry cannot flourish without universal access of electricity among the population. Therefore, increasing access of electricity regardless where the population live is crucial to distribute wealth throughout the archipelago. The lack of access to electrical power in remote areas is primarily due to sparse population all over the country and limited power infrastructure. Additionally, most are generated by centralized power plants and therefore making it difficult to be distributed evenly to the entire country due to its archipelagic nature. Consequently, diesel fuel is used to generate power in remote areas, raising the cost of generation of electricity significantly while hindering the local community to get equitable and reliable access of electricity. Our solution to this particular problem is to develop distributed power generation system where each small areas will be provided with their own electrical power generator. This distributed power generation system is not only powered by local renewable energy source but it will also enhance the economic activities in the area. Distributed power generation will also contribute to a more equitable, reliable, affordable, and sustainable electricity in remote areas. By promoting distributed renewable energy in Indonesia, we believe that it will bring about the transition to the use of renewable energy source to generate electrical power in the entire country.